2004
DOI: 10.1897/02-486
|View full text |Cite
|
Sign up to set email alerts
|

The effects of low hardness and pH on copper toxicity to Daphnia magna

Abstract: The majority of metal toxicity data available for freshwater organisms have been generated in laboratory water at pH > 6.5 and hardness > 50 mg/L as CaCO3. Extrapolation of these results to soft surface waters (i.e., hardness < or = 40 mg/L as CaCO3), similar to predominant conditions in the southeastern United States, may prove challenging. For example, South Carolina has surface waters that average 20 mg/L as CaCO3, and exist at extremes of 1 and 600 mg/L as CaCO3. This research characterized the acute toxic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
26
0

Year Published

2005
2005
2015
2015

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 40 publications
(29 citation statements)
references
References 12 publications
3
26
0
Order By: Relevance
“…This well agrees with the works of other researchers [5,6,19]. As pH decreases, the toxicity of Cu(II) increases due to increase of toxic free copper ions (Cu 2+ ) [19]. For Cr(VI), toxicity to D. magna was decreased at both pH 6 and 8 compared with that of pH 7.…”
Section: Individual Effects Of Ph Doc and Hardnesssupporting
confidence: 92%
See 1 more Smart Citation
“…This well agrees with the works of other researchers [5,6,19]. As pH decreases, the toxicity of Cu(II) increases due to increase of toxic free copper ions (Cu 2+ ) [19]. For Cr(VI), toxicity to D. magna was decreased at both pH 6 and 8 compared with that of pH 7.…”
Section: Individual Effects Of Ph Doc and Hardnesssupporting
confidence: 92%
“…This reduction of Cu(II) toxicity is caused by increase of complex formation between Cu(II) and DOC [5]. In general, copper associated with organic matter is considered to be non-bioavailable or non-toxic to aquatic organisms [19]. Contrary to Cu(II) toxicity, Cr(VI) toxicity was not influenced by DOC concentration.…”
Section: Individual Effects Of Ph Doc and Hardnessmentioning
confidence: 98%
“…A recent study has demonstrated an inverse relationship between copper toxicity of D. magna and hardness. Low concentrations of hardness, ranging from 7 to 50 mg/L as CaCO 3 , significantly affected the copper toxicity [21]. Therefore, it is clear that hardness is a major factor affecting metal toxicity and should be considered in determining reference LC 50 values when the toxicities of metal mixtures on aquatic species are evaluated.…”
Section: Mixture Toxicity Of Heavy Metalsmentioning
confidence: 99%
“…With the exception of research published by Long et al (2004) and Van Genderen et al (2005), there has been very little BLM work done in low hardness waters. Long et al (2004) investigated the effects of low hardness and pH on copper toxicity to Daphnia magna.…”
Section: Blm Application In Very Low Hardness Watersmentioning
confidence: 99%
“…With the exception of research published by Long et al (2004) and Van Genderen et al (2005), there has been very little BLM work done in low hardness waters. Long et al (2004) investigated the effects of low hardness and pH on copper toxicity to Daphnia magna. They prepared one set of synthetic water that had the same pH and varied the hardness (7.9 to 50 .7 mg/l) and a second set of synthetic waters that either had a hardness of 7.1 or 20.6 mg/l.…”
Section: Blm Application In Very Low Hardness Watersmentioning
confidence: 99%